Mengatasi perilaku kerja kontraproduktif melalui peran integratif politik organisasional dan kecerdasan emosional pada era revolusi industri 4.0 - Sunargo Sunargo; Dwi Hastuti (Jurnal Paradigma Ekonomika, 2019)
Counterproductive work behavior is a common phenomenon that is a problem in human resources. Such work behavior can be considered through situational and individual factors. The workplace environment situation that contains political activity and individual ability who have emotional intelligence can determine work behavior. This study examines the influence of perceived organizational politics on counterproductive work behavior and examines the role of moderation on that effect. The test was carried out using data of 200 employee respondents who worked at companies in the Batam industrial area. Results of the study using hierarchical regression analysis show that perceived organizational politics have a positive and significant effect on counterproductive work behavior. Furthermore, emotional intelligence can mitigate counterproductive work behavior caused by organizational political situations. This research provides practical benefits in overcoming the problem of counterproductive work behavior